Дерев’янко Василь Миколайович (до 60-річчя від дня народження) - Бойко, М.Ф.; Черевченко, Т.М.; Левон, Ф.М.; Косенко, І.С.; Ходосовцев, О.Є.; Ільєнко, О.О.; Галкін, С.І.; Мойсієнко, І.І.; Свиденко, В.А.; Свиденко, Л.В.; Карнатовська, М.Ю.; Худолєй, В.М. (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
Дерев’янко Василь Миколайович (до 60-річчя від дня народження)